Hubungan Emotional Quotient dengan Indeks Prestasi Kumulatif Mahasiswa Angkatan 2020 Fakultas Kedokteran Universitas Sam Ratulangi - Winengko, Livia C.; Homenta, Heriyannis; Berhimpon, Siemona L. E. (Medical Scope Journal, 2025)
Abstract: Emotional quotient (EQ) is the ability to understand and control emotions in oneself and others. The essentials to develop EQ are superior in medical students due to future work professions that require skills to maintain interactions with patients and other medical workers. This study aimed to evaluate the correlation between EQ and the Cumulative Achievement Index in medical students class of 2020, Faculty of Medicine, Universitas Sam Ratulangi. This was an observational  and analytical study with a cross-sectional design. Samples were 160 students from the class of 2020 at the Faculty of Medicine, Universitas Sam Ratulangi. The EQ value was measured using the TEIQue-SF instrument, while the Cumulative Achievement Index was obtained from the student transcripts. The result showed that most of the students have moderate EQ (77.5%) and Cumulative Achievement Index that predicated with a compliment (55%). There was an insignificant correlation between EQ and the Cumulative Achievement Index (p=0.506; r=0.053), and the correlation was positive and very weak. In conclusion, there is a positive but insignificant correlation between EQ and Cumulative Achievement Index among students class of 2020, Faculty of Medicine, Universitas Sam Ratulangi. Keywords: Emotional Quotient; Cumulative Achievement Index; Trait Emotional Intelligence Questionnaire-Short Form   Abstrak: Emotional Quotient (EQ) adalah kemampuan memahami dan mengendalikan emosi pada diri sendiri dan orang lain. Kebutuhan untuk mengembangkan EQ yang lebih tinggi pada mahasiswa Fakultas Kedokteran karena profesi kinerja ke depannya membutuhkan keterampilan guna membangun interaksi dengan pasien dan tenaga medis lainnya. Penelitian ini bertujuan untuk mengevaluasi hubungan EQ dengan Indeks Prestasi Kumulatif (IPK) mahasiswa angkatan 2020 Fakultas Kedokteran Universitas Sam Ratulangi (FK Unsrat). Penelitian ini menerapkan pendekatan observasional analitik dan studi potong lintang. Sampel penelitian ialah 160 mahasiswa angkatan 2020 FK Unsrat. Nilai EQ diukur menggunakan instrumen TEIQue-SF dan nilai IPK diperoleh dari transkip nilai mahasiswa. Hasil penelitian memperlihatkan bahwa sebagian besar mahasiswa memiliki EQ kategori sedang (77,5%) dan predikat IPK dengan pujian (55%). Terdapat hubungan tidak bermakna antara EQ dengan IPK kekuatan korelasi sangat lemah dan arah korelasi positif (p=0,506; r=0,053). Simpulan penelitian ini ialah terdapat hubungan positif yang tidak bermakna antara Emotional Quotient dengan Indeks Prestasi Kumulatif mahasiswa angkatan 2020 Fakultas Kedokteran Universitas Sam Ratulangi. Kata kunci: Emotional Quotient; Indeks Prestasi Kumulatif; Trait Emotional Intelligence Questionnaire-Short Form